Karakterisasi dari Properti Larutan Garam dengan Range Finder Ultrasonik Menggunakan Metode Transformasi Fourier - Ihwan Dwi Wicaksono; Agus Indra Gunawan; Bima Sena Bayu Dewantara (Jurnal Rekayasa Elektrika, 2020)
In this paper we characterize the saline solution using Range Finder Ultrasonic (RFU). RFU is one kind of ultrasonic transducer that requires air as a transmission medium and commonly are used to determine distances. The advantages of this transducer are cheap and common in local market. Since it uses air as medium, the signal which is produced by transducer are easy to shape shift and has a very long noise tail wave. This phenomenon was seen in previous studies, when the transducer position was slightly shifted, the shape of the echo signal became very different. In this paper, we modified the input signal from the technique in the previous paper to improve the echo signal. Some modification of trigger signal from transmitter models were done, then calculate the echo signal to ensure the signal have smallest Signal to Noise Ratio (SNR) and noise tail wave. Furthermore, we did filtering process from echo signal and calculating using Fourier Transform which are performed to obtain accurate echo signal information of 40 KHz frequency. The results of this experiment is an improvement in the average error of calibration curve 0.1224221 (Vrms) and 0.14383881 (Vpeak). While the average error of the results of the normalization of the magnitude Fourier Transform of 40 KHz frequency is equal to 0.096973114.